Discomfort Food : The Culinary Imagination in Late Nineteenth-Century French Art - Kessler, Marni Reva (Book collections on Project MUSE., 2021)
"An intricate and provocative journey through nineteenth-century depictions of food and the often uncomfortable feelings they evoke"--